The Production and Inventory Behavior of the American Automobile Industry - Blanchard, Olivier J. (Journal of Political Economy, 1983)
Understanding inventory movements is central to an understanding of business cycles. This paper presents an empirical study of the behavior of inventories in the automobile industry. It finds that inventory behavior is well explained by the assumption of intertemporal optimization with rational expectations. The underlying cost structure appears to have substantial costs of changing production as well as substantial costs of being away from target inventory, the latter being a function of current sales. Given this cost structure, whether inventory behavior is stabilizing or destabilizing depends on the characteristics of the demand process. In the automobile industry, inventory behavior is destabilizing: the variance of production is larger than the variance of sales.